ICG angiography predicts burn scarring within 48 h of injury in a porcine vertical progression burn model. Issue 5 (August 2015) - Fourman, Mitchell S.; McKenna, Peter; Phillips, Brett T.; Crawford, Laurie; Romanelli, Filippo; Lin, Fubao; McClain, Steve A.; Khan, Sami U.; Dagum, Alexander B.; Singer, Adam J.; Clark, Richard A.F.
Highlights We compare indocyanine green and laser Doppler in the prediction of burn scarring. We utilized a validated vertical progression porcine burn model. Indocyanine green fluorescence predicted burn contraction within 2 days of injury. Laser Doppler failed to show significant predictive potential. Human studies necessary to discern full utility of ICG angiography in burns.